Step
*
2
2
1
1
of Lemma
flip-adjacent
1. n : ℕ
2. ∀k:ℕ. ∀j:ℕn. ∀i:ℕj.
     (((j - i) ≤ k) 
⇒ (∀f:ℕn ⟶ ℕn. ∃L:ℕn - 1 List. (((i, j) o f) = reduce(λi,g. ((i, i + 1) o g);f;L) ∈ (ℕn ⟶ ℕn))))
3. i : ℕn
4. j : ℕn
5. ¬i < j
6. j < i
7. L : ℕn - 1 List
8. ((j, i) o (λx.x)) = reduce(λi,g. ((i, i + 1) o g);λx.x;L) ∈ (ℕn ⟶ ℕn)
⊢ (i, j) = ((j, i) o (λx.x)) ∈ (ℕn ⟶ ℕn)
BY
{ ((FunExt THEN Reduce 0) THEN Auto) }
1
1. n : ℕ
2. ∀k:ℕ. ∀j:ℕn. ∀i:ℕj.
     (((j - i) ≤ k) 
⇒ (∀f:ℕn ⟶ ℕn. ∃L:ℕn - 1 List. (((i, j) o f) = reduce(λi,g. ((i, i + 1) o g);f;L) ∈ (ℕn ⟶ ℕn))))
3. i : ℕn
4. j : ℕn
5. ¬i < j
6. j < i
7. L : ℕn - 1 List
8. ((j, i) o (λx.x)) = reduce(λi,g. ((i, i + 1) o g);λx.x;L) ∈ (ℕn ⟶ ℕn)
9. x : ℕn
⊢ ((i, j) x) = ((j, i) x) ∈ ℕn
Latex:
Latex:
1.  n  :  \mBbbN{}
2.  \mforall{}k:\mBbbN{}.  \mforall{}j:\mBbbN{}n.  \mforall{}i:\mBbbN{}j.
          (((j  -  i)  \mleq{}  k)
          {}\mRightarrow{}  (\mforall{}f:\mBbbN{}n  {}\mrightarrow{}  \mBbbN{}n.  \mexists{}L:\mBbbN{}n  -  1  List.  (((i,  j)  o  f)  =  reduce(\mlambda{}i,g.  ((i,  i  +  1)  o  g);f;L))))
3.  i  :  \mBbbN{}n
4.  j  :  \mBbbN{}n
5.  \mneg{}i  <  j
6.  j  <  i
7.  L  :  \mBbbN{}n  -  1  List
8.  ((j,  i)  o  (\mlambda{}x.x))  =  reduce(\mlambda{}i,g.  ((i,  i  +  1)  o  g);\mlambda{}x.x;L)
\mvdash{}  (i,  j)  =  ((j,  i)  o  (\mlambda{}x.x))
By
Latex:
((FunExt  THEN  Reduce  0)  THEN  Auto)
Home
Index